Ringlegged Earwig, Euborellia annulipes (Lucas) (Insecta: Dermaptera: Carcinophoridae) - John L. Capinera (EDIS)
This is the most common earwig in Florida, and probably the only species that could be considered to be a pest, though it rarely builds to very high numbers. It is mostly known as a nuisance, and the small amount of plant feeding injury it causes likely is offset by its beneficial predatory habits. This document is EENY-088, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 1999. Reviewed: May 2003.